Diagnóstico del consumo de energía eléctrica en la empresa de fabricación de helados kedely de la ciudad de Quito durante el año 2015. Diseño de un plan de mejoras en la gestión energética para el portador eléctrico. - Flores Asimbaya, Luis Antonio (2016)
This research was realized at the ice cream factory called Kedely which is located in Quito City; the inclusion of energy efficiency within the microenterprise drove us to use the model ISO50001. When the objective of design an energy management improvement plan for the electrical carrier which we reduce costs for electric consumption was done, An audit was done in the factory, the graphics control were determined, data acquisition with the use of the energy quality analyzer Fluke 435 Series II, electrical diagrams modelling and simulation by the use of the Software EasyPower, through that improvement opportunities were got, like the productive losses in the power offset losses in the copper, the lack of maintenance in cold rooms and the illumination optimization, with this proposal an energy management improvement plan for the electrical carrier was structured. An energy policy was defined, a parameter monitoring system was designed, an equipment maintenance program which consume higher power and suggesting the energy indicator establishment, which we will achieve an annual energy save of 13.15% in the billing for electric consumption in 2015. The financial indicators showed us the the project is viable, with an investment recovery period IRP of 1year 2 month and 11 days, a present positive value PPV and an internal return rate IRR higher than the discount rate.